Synergy between dihydromyricetin intervention and irinotecan chemotherapy delays the progression of colon cancer in mouse models. Issue 4 (25th March 2019) - Zhu, Xiao-Hui; Lang, He-Dong; Wang, Xiao-Lan; Hui, Suo-Cheng; Zhou, Min; Kang, Chao; Yi, Long; Mi, Man-Tian; Zhang, Yong
Abstract : Dihydromyricetin may be a favorable chemotherapeutic coadjuvant agent to reduce colonic tumors via different mechanisms in two mouse models. Abstract : Colorectal cancer (CRC) is the third highest cause of cancer-related death and the main option for prolonged survival is chemotherapeutic intervention. There is increasing interest in dietary intervention using natural agents to enhance the sensitivity of such invasive chemical treatment. In this study, the chemotherapeutic efficacy of dihydromyricetin (DMY) intervention on treatments involving irinotecan (CPT-11) or gemcitabine (GM) was evaluated in an AOM/DSS-induced colitis-associated colon cancer model and a Min (Apc Min/+) mice model. Our data showed that DMY could promote the CPT-11 effect both in the mouse model of AOM/DSS and Apc Min/+ cancer and had no influence on the GM effect. In AOM/DSS cancer, tumors were sensitive to 100 mg kg −1 DMY chemotherapy under 100 mg kg −1 or 200 mg kg −1 CPT-11. DMY-driven CPT-11 chemotherapy induced enhanced IgG levels and the reduction of Fusobacterium abundance in the gut. In the Min model, CPT-11 with 20 mg kg −1 DMY prevented tumor formation but not with 100 mg kg −1 DMY. Mechanically, chloride ion-dependent CFTR, CLCN4, and CLIC4 signaling are not involved in DMY mediated chemotherapeutic colon tumorigenesis. These results suggested that a suitable dose of DMY could act as a coadjuvant to CPT-11 chemotherapy.